Acute Oral Toxicity Assessment of Rutinoside on Renal Histopathology in Wistar Rats - Rena Normasari; Yulia Pratiwi (Indonesian Journal Publisher, 2026)
This study aimed to evaluate the acute oral toxicity of rutinoside by assessing renal histopathological changes in Wistar rats. Twelve Wistar rats (Rattus norvegicus), consisting of equal numbers of males and females and aged approximately three months, were randomly assigned to control and treatment groups. After an acclimatization period under standard laboratory conditions, the treatment group received a single oral dose of rutinoside (5000 mg/kg body weight) via gastric gavage in accordance with OECD Guideline 423, while the control group received the vehicle only. Animals were observed daily for 14 days for mortality, behavioral changes, and clinical signs of toxicity. At the end of the observation period, rats were euthanized, and both kidneys were collected for histopathological evaluation. Kidney tissues were fixed in 10% buffered formalin, processed, and stained with hematoxylin and eosin. Histological examination was performed at 400× magnification using a standardized scoring system, and statistical analysis was conducted using the Mann–Whitney U test. No mortality or treatment-related clinical signs were observed during the study period. Histopathological findings demonstrated no significant differences between the control and rutinoside-treated groups. Renal structures, including glomeruli and tubules, remained intact, with no evidence of degeneration, inflammation, or other pathological alterations. In conclusion, acute oral administration of rutinoside at a high dose did not induce renal toxicity in Wistar rats, suggesting a favorable acute safety profile. Further studies are required to evaluate the safety of rutinoside following repeated or long-term exposure.